Different conjugated system Cd(II)/Hg(II) Schiff base complexes: syntheses, supramolecular metal−organic frameworks, luminescent properties and DFT study - Dong, Yu-Wei; Wang, Ping; Fan, Rui-Qing; Chen, Wei; Wang, A-Ni; Yang, Yu-Lin (Journal of coordination chemistry, 2017)
A series of different conjugated systems of 2D/3D supramolecular metal-organic frameworks (SMOFs) are constructed by C/O−H⋯Cl hydrogen bonds and π⋯π interactions. These complexes, [HgL 1 Cl 2 ] (1), [HgL 2 Cl 2 ] (2), [HgL 3 Cl 2 ] (3), [CdL 4 Cl 4 ] 2 (4), and [CdL 5 Cl 2 (CH 3 OH)] (5), have been synthesized and characterized by single-crystal X-ray diffraction, 1 H NMR, FT-IR, and EA. The X-ray diffraction analyses reveal that 1 features a 3D supramolecular framework with {4 4 ·6 6 } topology structure, while 2, 3, and 5 exhibit 3D 6-connected {4 12 ·6 3 } topology structures. Complex 4 shows a two-dimensional layer with 4 4 topology structure. Based on these varied structures caused by different conjugated system, the emission maximum wavelengths of 1-5 can be tuned in a large range of 492-587 nm. Both electron-donating ability and the conjugated system in general can support λ em shift to red direction. In order to have better understanding of electronic transitions of the complexes, a time-dependent DFT study has been performed. The enhancement of the fluorescence intensities for the complexes compared to the ligands indicates potential to serve as photoactive materials.